Factor analysis of the Lithuanian equity market indices - Danilenko , Svetlana (Lietuvos matematikos rinkinys, 2009)
Statistical measures that can reproduce the state of the stock market and the tendencies of its change dynamics are the stock indexes. Having in mind the more complicated state of the finance system it is important to answer the question of what impacts the fluctuations of the stock prices. The article discusses various factors that impact the fluctuations of the Lithuanian stock index OMXV ; also stock index factor analysis is performed. Factors are determined using the main components method.